Analisis Brand Image Universitas Muhammadiyah Mataram sebagai Perguruan Tinggi Swasta (PTS) di Nusa Tenggara Barat - Muhammad Rahmatul Burhan; Isra Dewi Kuntary Ibrahim (Universitas Bumigora, 2022)
The history of the University of Muhammadiyah Mataram (UMMAT) does not match the UMMAT brand image in the eyes of the public. The purpose of this study was to determine the brand image of UMMAT and its advantages and disadvantages as private universities in NTB. This research is qualitative and uses coding for data analysis techniques. The main data were obtained from purposively selected informants and snowball sampling to assess ten elements of brand image. The analyzed data has gone through the triangulation stage. In this study, it was found that the students' assessment of UMMAT was divided into two groups of students. First, students who take part in the Student Activity Unit (UKM). Second, students who do not participate in campus UKM. Brand awareness and brand association still need to be improved to achieve brand familiarity in the eyes of the wider community. However, the positive thing is that brand trust and brand loyalty from the community are already attached. UMMAT needs to increase the intensity of advertising activities with effective communication. Then UMMAT should encourage all groups of students to contribute in disseminating information from campus in any form to the public. Because it has limitations, it is hoped that future researchers can develop this research with different methods and techniques so as to enrich references in science.